Positive electrode slurry, preparation method thereof, positive plate and lithium ion battery

By adding polyacrylate polymer additives to the slurry of high-nickel positive electrode material, the problems of unstable slurry viscosity and poor coating consistency are solved, and the stability of the slurry and battery performance are improved.

CN119560563APending Publication Date: 2025-03-04LISHEN BATTERY (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411724115.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The high surface residual alkali content of high nickel positive electrode materials leads to unstable viscosity of the positive electrode slurry and poor consistency of coating performance. The existing acid additives can only neutralize residual alkali and cannot effectively improve the stability of the slurry.

Method used

Add polyacrylate polymer additive to the positive electrode slurry to prevent residual alkali from attacking the PVDF binder, avoid slurry gel, and partially replace PVDF to achieve reliable bonding performance and stability.

Benefits of technology

It significantly improves the stability of the positive electrode slurry, improves viscosity changes and settlement problems, and improves coating consistency and overall battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560563A_ABST
    Figure CN119560563A_ABST
Patent Text Reader

Abstract

The invention discloses positive electrode slurry. The positive electrode slurry comprises a solid component and a solvent, the solid component comprises a positive electrode material, a conductive agent, a binder and an additive; the positive electrode material comprises a nickel-cobalt-manganese NCM ternary material and / or a nickel-cobalt-aluminum NCA ternary material; in the positive electrode material, the ratio range of the nickel content is that the nickel content is greater than or equal to 80% and less than 100%; the additive is a polyacrylate polymer additive; the solid component comprises the following components in percentage by mass: 91%-98% of a positive electrode material, 0.1%-4% of a conductive agent, 0.5%-3% of a binder and 0.02%-2% of an additive. The solvent is N-methyl pyrrolidone. According to the technical scheme, residual alkali is prevented from attacking PVDF serving as a positive electrode binder, slurry gel is effectively avoided, PVDF can be partially replaced, reliable binding performance is achieved, the stability of the slurry is obviously improved, and the overall performance of a battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode slurry and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] At present, lithium-ion batteries are widely used in various electric vehicles and consumer electronic products. As consumers' requirements for car range continue to increase and the standby time of electronic devices increases, increasing the energy density of batteries is an inevitable trend.

[0003] The use of high-capacity positive electrode materials is the most effective solution to increase battery energy density. Currently, high-nickel NCM (nickel cobalt manganese) and NCA (nickel cobalt aluminum) materials have become the first choice for positive electrode materials used in batteries for high-end electric vehicles and consumer electronics.

[0004] It should be noted that high-nickel positive electrode materials refer to NCM (nickel cobalt manganese) and NCA (nickel cobalt aluminum) materials with a nickel content (mass content) greater than 80%.

[0005] However, for high-nickel positive electrode materials, the content of residual alkali (lithium hydroxide LiOH, lithium carbonate Li2CO3) on their surface is high, which produces chemical cross-linking with PVDF (polyvinylidene fluoride) as the positive electrode binder, resulting in unstable viscosity of the positive electrode slurry, which in turn leads to poor consistency in the coating performance of the positive electrode slurry and even makes it impossible to produce positive electrode sheets normally. This is a prominent problem in the practical application of high-nickel positive electrode materials.

[0006] In order to solve the gel problem in the slurry of high-nickel positive electrode materials, the battery production industry mainly adds acid additives (such as oxalic acid, maleic acid, etc.) to react with the residual alkali on the surface of high-nickel positive electrode materials. In this process, acid additives can only play an acid-base neutralization role and have no positive effect on the stability of the slurry. In addition, the addition of such additives has a negative impact on the gas production and performance of the battery system, which is not conducive to the performance of the battery cell.

[0007] Therefore, given that acid additives can only play an acid-base neutralization role and have a negative impact on slurry stability and battery performance, there is an urgent need to develop a technology that can solve this technical problem. Summary of the invention

[0008] The purpose of the present invention is to provide a positive electrode slurry and a preparation method thereof, a positive electrode sheet and a lithium ion battery in view of the technical defects existing in the prior art.

[0009] To this end, the present invention provides a positive electrode slurry, characterized in that it includes a solid component and a solvent;

[0010] Among them, the solid components include positive electrode materials, conductive agents, binders and additives;

[0011] The positive electrode material includes a nickel-cobalt-manganese (NCM) ternary material and / or a nickel-cobalt-aluminum (NCA) ternary material;

[0012] In the positive electrode material, the nickel content is in the range of: 80%≤nickel content<100%;

[0013] The additive is a polyacrylate polymer additive;

[0014] The solid component comprises 91% to 98% by mass of positive electrode material, 0.1% to 4% of conductive agent, 0.5% to 3% of binder and 0.02% to 2% of additive;

[0015] Wherein, the solvent is N-methylpyrrolidone.

[0016] In addition, the present invention also provides a method for preparing the positive electrode slurry as described above, characterized in that it comprises the following steps:

[0017] The first step is to add polyvinylidene fluoride PVDF as a binder and a polyacrylate polymer additive into N-methylpyrrolidone solvent, and stir them thoroughly to obtain a polyvinylidene fluoride PVDF glue solution containing a polyacrylate polymer additive;

[0018] The second step is to continue adding conductive carbon black as a conductive agent into the polyvinylidene fluoride PVDF glue solution and stir it thoroughly;

[0019] The third step is to continue adding positive electrode materials and stir thoroughly to obtain the required positive electrode slurry.

[0020] In addition, the present invention also provides a positive electrode sheet, which includes a positive electrode current collector;

[0021] The surface of the positive electrode current collector is coated with at least one layer of the positive electrode slurry as described above.

[0022] In addition, the present invention also provides a lithium-ion battery, which includes the positive electrode sheet as described above;

[0023] The positive electrode sheet is formed by coating the positive electrode slurry as mentioned above on the surface of the positive electrode current collector.

[0024] It can be seen from the technical solution provided by the present invention that, compared with the prior art, the present invention provides a positive electrode slurry and a preparation method thereof, a positive electrode sheet, and a lithium ion battery. In the present invention, a polyacrylate polymer additive (including but not limited to a homopolymer or copolymer formed by polymerization of acrylic acid and its ester derivatives or other derivatives) is added to the positive electrode slurry. Its addition not only prevents residual alkali from attacking PVDF (polyvinylidene fluoride) as a positive electrode binder, and effectively avoids the occurrence of slurry gel, but also can partially replace PVDF (polyvinylidene fluoride), achieve reliable bonding performance, significantly improve the stability of the slurry, improve the common problems of large slurry viscosity changes and sedimentation, improve coating consistency, and thus improve the overall performance of the battery, which has great practical significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A flow chart of a method for preparing a positive electrode slurry provided by the present invention;

[0026] Figure 2 Schematic diagram of the shear strain curve of the positive electrode slurry prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation modes.

[0030] The present invention provides a positive electrode slurry, comprising a solid component and a solvent;

[0031] Among them, the solid components include positive electrode materials, conductive agents, binders and additives;

[0032] The positive electrode material includes a nickel-cobalt-manganese (NCM) ternary material and / or a nickel-cobalt-aluminum (NCA) ternary material;

[0033] In the positive electrode material, the nickel content (mass content) is in the range of: 80%≤nickel content<100%;

[0034] The conductive agent is conductive carbon black SP;

[0035] The binder is polyvinylidene fluoride (PVDF);

[0036] The additive is a polyacrylate polymer additive;

[0037] The solid component comprises 91% to 98% by mass of positive electrode material, 0.1% to 4% of conductive agent, 0.5% to 3% of binder and 0.02% to 2% of additive.

[0038] Wherein, the solvent is N-methylpyrrolidone.

[0039] In the present invention, in specific implementation, the polyacrylate polymer additive includes but is not limited to a homopolymer or copolymer formed by polymerization of acrylic acid and its ester derivatives or other derivatives.

[0040] In specific implementation, polyacrylate can be a homopolymer or copolymer with acrylic ester as a monomer, for example, a homopolymer or copolymer with acrylic ester (such as acrylic acid) as a monomer.

[0041] It should be noted that polyacrylate is a homopolymer or copolymer with acrylate as a monomer, and the difference lies in the functional group modification. Acrylate includes acrylic acid, and acrylic acid includes methacrylic acid.

[0042] Furthermore, in a specific implementation, the polyacrylate polymer additive includes a polymer of at least one of 2-methylglutaric acid, 2-methylacrylic acid, and 3,3-dimethylacrylic acid.

[0043] It should be noted that the polyacrylate polymer additive may be a modified polymer of 2-methylglutaric acid, 2-methylacrylic acid, and / or 3,3-dimethylacrylic acid.

[0044] In Example 1 below, the polyacrylate polymer additive is 2-methylglutaric acid (a modified polymer).

[0045] In specific implementation, the polyacrylate polymer additive can include any of the following forms:

[0046] 1. Homopolymer formed by polymerization of acrylic acid;

[0047] 2. Copolymers formed by polymerization of acrylic acid and its ester derivatives;

[0048] 3. Homopolymers formed by polymerization of ester derivatives of acrylic acid;

[0049] In the above-mentioned homopolymers and copolymers, the mass ratio of each component before polymerization can be any percentage as long as the total is 100%.

[0050] In the present invention, in specific implementation, the solid content of the solid component in the positive electrode slurry is: 60% to 80% In order to prepare the positive electrode slurry provided by the present invention, refer to Figure 1 The present invention provides a method for preparing a positive electrode slurry, comprising the following steps:

[0051] The first step is to add polyvinylidene fluoride PVDF as a binder and a polyacrylate polymer additive into N-methylpyrrolidone solvent, and stir them thoroughly to obtain a polyvinylidene fluoride PVDF glue solution containing a polyacrylate polymer additive;

[0052] The second step is to continue adding conductive carbon black as a conductive agent into the polyvinylidene fluoride PVDF glue solution and stir it thoroughly;

[0053] The third step is to continue adding positive electrode materials and stir thoroughly to obtain the required positive electrode slurry.

[0054] In the first step, the polyacrylate polymer additive includes but is not limited to a homopolymer or copolymer formed by polymerization of acrylic acid and its ester derivatives or other derivatives.

[0055] In the third step, the positive electrode material includes a nickel-cobalt-manganese NCM ternary material and / or a nickel-cobalt-aluminum NCA ternary material;

[0056] In the positive electrode material, the nickel content (mass content) is in the range of: 80%≤nickel content<100%;

[0057] In the first to third steps, for the preparation method of the positive electrode slurry of the present invention, in the solid component (i.e., solute) of the positive electrode slurry, the mass percentages of the positive electrode material, the conductive agent, the binder and the additive are: (91-98): (0.1-4): (0.5-3): (0.02-2).

[0058] Based on the positive electrode slurry provided by the present invention, the present invention further provides a positive electrode sheet, which includes a positive electrode current collector;

[0059] The surface of the positive electrode current collector is coated with at least one layer of the positive electrode slurry as described above.

[0060] In a specific implementation, the positive electrode current collector is aluminum foil.

[0061] Based on the positive electrode sheet provided by the present invention, the present invention further provides a lithium ion battery, which comprises the positive electrode sheet as described above;

[0062] The positive electrode sheet is formed by coating the positive electrode slurry mentioned above on the surface of the positive electrode current collector.

[0063] In order to more clearly understand the technical solution of the present invention, the technical solution of the present invention is described below through specific embodiments.

[0064] The following is a description of the positive electrode slurry preparation method and lithium ion battery preparation process according to the present invention in combination with Example 1 and Comparative Example 1.

[0065] Comparative example 1.

[0066] The conventional method for preparing positive electrode slurry includes the following operations:

[0067] 1. Preparation of positive electrode slurry.

[0068] The first step is to add polyvinylidene fluoride PVDF as a binder and maleic acid as a positive electrode additive to N-methylpyrrolidone (NMP) solvent, and stir them thoroughly (for example, for 60 minutes) to obtain polyvinylidene fluoride PVDF glue solution to which maleic acid has been added;

[0069] In other words, the PVDF glue is prepared in advance.

[0070] Step 2: Continue to add conductive carbon black as a conductive agent into the polyvinylidene fluoride PVDF glue solution and stir it thoroughly (for example, stir for 60 minutes);

[0071] The third step is to continue adding the positive electrode material NCA and stir it evenly (specifically, stir it with a stirrer at a speed of 2500 rpm for 120 minutes) to finally obtain the required positive electrode slurry.

[0072] In Comparative Example 1, it should be noted that, for the positive electrode material, among the solid components thereof, the mass ratios of the positive electrode material NCM, the conductive agent, the binder PVDF and the positive electrode additive maleic acid are 96.7:2:1.2:0.1 respectively.

[0073] In Comparative Example 1, it should also be noted that the mass percentage of the solid component in the positive electrode slurry is 60% to 80%.

[0074] 2. Preparation of lithium-ion batteries.

[0075] The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and after drying, it is cold pressed, slit, wound, and assembled into a 21700-size lithium-ion battery of Comparative Example 1.

[0076] Example 1.

[0077] The method for preparing the positive electrode slurry provided by the present invention comprises the following operations:

[0078] 1. Preparation of positive electrode slurry

[0079] The first step is to add a binder polyvinylidene fluoride (PVDF) and a polyacrylate polymer additive to an N-methylpyrrolidone (NMP) solvent, and stir them thoroughly (for example, for 60 minutes) to obtain a polyvinylidene fluoride (PVDF) adhesive containing a polyacrylate polymer additive;

[0080] The polyacrylate polymer additive is 2-methylglutaric acid (a modified polymer).

[0081] In other words, the PVDF glue is prepared in advance.

[0082] Step 2: Continue to add conductive carbon black as a conductive agent into the polyvinylidene fluoride PVDF glue solution and stir it thoroughly (for example, stir for 60 minutes);

[0083] The third step is to continue adding high-nickel ternary positive electrode material NCM and stir it thoroughly (specifically, stir it with a stirrer at a speed of 2500 rpm for 120 minutes) to finally obtain the required positive electrode slurry.

[0084] In Example 1, it should be noted that, for the positive electrode material, the mass ratios of the positive electrode material NCM, the conductive agent, the binder PVDF and the polyacrylate polymer additive in the solid components thereof are 97:2:0.9:0.1 respectively. Due to the specific modified groups of the polyacrylate polymer material, part of the amount of PVDF used as the positive electrode binder can be replaced, and the binder function can be synergistically exerted, thereby increasing the proportion of the positive electrode active material and improving the battery design redundancy.

[0085] In Example 1, it should also be noted that the mass percentage of the solid component in the positive electrode slurry is 60% to 80%.

[0086] 2. Preparation of lithium-ion batteries.

[0087] The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and after drying, it is cold pressed, slit, wound, and assembled into a 21700-size lithium-ion battery of Example 1.

[0088] The following further describes the testing process of the positive electrode slurry obtained in Comparative Example 1 and Example, which specifically includes the following tests:

[0089] 1. Anti-gel test of positive electrode slurry The positive electrode slurries prepared in Example 1 and Comparative Example 1 were placed in an environment with a temperature of 30° C. and a humidity of 30% for 24 hours, and the state of the positive electrode slurries was observed.

[0090] 2. Positive electrode slurry stability test: Take 200 ml of each of the positive electrode slurries prepared in Example 1 and Comparative Example 1, monitor the changes in viscosity and solid content during standing, and use a rheometer to test the elastic modulus, phase angle, cohesive energy and other physical properties of the slurry to characterize the stability of the slurry.

[0091] The specific test results of Example 1 and Comparative Example 1 are shown in Table 1 below.

[0092] Table 1

[0093]

[0094] 3. Physical property test of the electrode. Compared with comparative example 1, Example 1 reduces the amount of PVDF used, but the bonding force is increased from 30gf in comparative example 1 to 40gf, and the flexibility of the electrode is increased from passing through a 3mm steel rod in comparative example 1 to passing through a 2mm steel rod. It should be noted that under the design of the positive electrode system, passing through a 2mm steel rod is a huge improvement.

[0095] 4. The performance comparison test results of the 21700 lithium-ion batteries prepared in Example 1 and Comparative Example 1 are shown in Table 2 below.

[0096] Table 2

[0097]

[0098] Practical tests and Table 1 prove that in the positive electrode slurry of Example 1, by adding the polyacrylate polymer additive, after standing for 24 hours, the viscosity of the positive electrode slurry changes little, no obvious sedimentation occurs, and a good flow state is still maintained. However, the viscosity of the positive electrode slurry of Comparative Example 1 changes greatly, the slurry sedimentation becomes larger, and the fluidity becomes significantly worse after standing for 40 hours, showing a gel state. This poor gel easily leads to poor consistency in the coating performance of the positive electrode slurry.

[0099] It can be seen from Table 2 above that for the present invention, the polyacrylate polymer additive has significant technical advantages compared with maleic acid, and can greatly improve the positive electrode capacity, ACR (AC internal resistance), DCIR (DC internal resistance) and cycle life, while the other properties remain the same.

[0100] Figure 2 Schematic diagram of shear strain curves of the positive electrode slurries prepared in Example 1 and Comparative Example 1.

[0101] See also Figure 2 As shown, the cohesive energy of the positive electrode slurry of Example 1 is 39.63Pa, and the cohesive energy of the positive electrode slurry of Comparative Example 1 is 0.83Pa.

[0102] It should be noted that see Figure 2 As shown, the elastic modulus of the slurry of Example 1 of the present invention is basically maintained at the same level without significant decrease, while the slurry of Comparative Example 1 is significantly reduced, indicating that the slurry of the present invention has not undergone significant changes in viscoelastic state, and the slurry of the present invention maintains good structure and stability. The rheological tester fits and calculates the cohesive energy of the slurry based on the storage modulus and shear strain curve, and the results obtained are: the cohesive energy of the positive electrode slurry of Example 1 is 39.63Pa, and the cohesive energy of the positive electrode slurry of Comparative Example 1 is only 0.83Pa.

[0103] It should be noted that the greater the cohesive energy of the positive electrode slurry, the stronger the force between the particles, the tighter the combination, and the better the stability of the slurry, which is consistent with the measured sedimentation data. The phase angle, Example 1, is basically unchanged, the particles tend to be evenly dispersed, and the fluidity is good. However, the maleic acid has a significant increase, the particles tend to be stratified, and the flow is uneven. Therefore, the addition of polyacrylate polymer additives has a significant effect on the stability of the positive electrode slurry.

[0104] In summary, compared with the prior art, the positive electrode slurry and preparation method, positive electrode sheet, and lithium-ion battery provided by the present invention, after using the polyacrylate polymer additive, can effectively exert the anti-gel effect and significantly improve the slurry stability, effectively solve the problems of poor coating consistency and low pass rate caused by slurry sedimentation in production, thereby improving the overall performance of the battery, and after achieving full replacement, after inspection, the proportion of active substances can be increased by 0.3%, and the battery cost can be reduced by 17%, which significantly improves the competitiveness of battery products and the profits of battery manufacturers.

[0105] For the present invention, the polyacrylate polymer additive used in the present invention can not only replace the acid additive to achieve the anti-gel effect, but also improve the stability of the slurry and the battery performance. The role of the polyacrylate polymer additive in improving the stability of the slurry and the battery performance is something that the acid additive cannot do.

[0106] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A positive electrode slurry, characterized in that: including solid components and solvents; Among them, the solid components include positive electrode materials, conductive agents, binders and additives; The positive electrode material includes a nickel-cobalt-manganese (NCM) ternary material and / or a nickel-cobalt-aluminum (NCA) ternary material; In the positive electrode material, the nickel content is in the range of: 80%≤nickel content<100%; The additive is a polyacrylate polymer additive; The solid component comprises 91% to 98% by mass of positive electrode material, 0.1% to 4% of conductive agent, 0.5% to 3% of binder and 0.02% to 2% of additive; Wherein, the solvent is N-methylpyrrolidone.

2. The positive electrode slurry according to claim 1, characterized in that Polyacrylate polymer additives include homopolymers or copolymers formed by polymerization of acrylic acid and its ester derivatives or other derivatives.

3. The positive electrode slurry according to claim 1, characterized in that The solid content of the solid component in the positive electrode slurry is: 60% to 80%; and / or, The conductive agent is conductive carbon black SP; The binder is polyvinylidene fluoride (PVDF); and / or, Polyacrylate polymer additives include homopolymers or copolymers with acrylate as monomer.

4. The positive electrode slurry according to claim 1, characterized in that The polyacrylate polymer additive comprises a polymer of at least one of 2-methylglutaric acid, 2-methylacrylic acid, and 3,3-dimethylacrylic acid.

5. A method for preparing a positive electrode slurry according to any one of claims 1 to 4, characterized in that: The following steps are involved: The first step is to add polyvinylidene fluoride PVDF as a binder and a polyacrylate polymer additive into N-methylpyrrolidone solvent, and stir them thoroughly to obtain a polyvinylidene fluoride PVDF glue solution containing a polyacrylate polymer additive; The second step is to continue adding conductive carbon black as a conductive agent into the polyvinylidene fluoride PVDF glue solution and stir it thoroughly; The third step is to continue adding positive electrode materials and stir thoroughly to obtain the required positive electrode slurry.

6. The method for preparing the positive electrode slurry according to claim 5, characterized in that: In the first step, the polyacrylate polymer additive includes a homopolymer or copolymer formed by polymerization of acrylic acid and its ester derivatives or other derivatives.

7. The method for preparing the positive electrode slurry according to claim 5, characterized in that: In the third step, the positive electrode material includes a nickel-cobalt-manganese NCM ternary material and / or a nickel-cobalt-aluminum NCA ternary material; In the positive electrode material, the nickel content is in the range of: 80%≤nickel content<100%; In the solid components of the positive electrode slurry, the mass percentages of the positive electrode material, the conductive agent, the binder and the additive are: (91-98): (0.1-4): (0.5-3): (0.02-2).

8. A positive electrode sheet, characterized in that: including a positive electrode current collector; The surface of the positive electrode current collector is coated with at least one layer of the positive electrode slurry according to any one of claims 1 to 4.

9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode current collector is aluminum foil.

10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 8 or 9; The positive electrode sheet is formed by coating the positive electrode slurry as claimed in claims 1 to 3 on the surface of the positive electrode current collector.